Effect of molybdenum treatment on the element uptake of food crops in a long-term field experiment - Puskás-Preszner, Anita; Kovács, Béla; Andrási, Dávid; Burján, Zita Kata (Acta Agraria Debreceniensis, 2011)
Molybdenum, as a constituent of several important enzymes, is an essential microelement. It can be found in all kind of food naturally at low levels. However, environmental pollution, from natural or anthropogenic sources, can lead to high levels of the metal in plants. Our study is based on long-term field experiments at Nagyhörcsök, where different levels of soil contamination conditions are simulated. Plant samples were collected from the experiment station to study the behavior of elements: uptake by and transport within the plants, accumulation in different organs, phytotoxicity and effects on the quantity and quality of the crop. In this study, we present the effect of molybdenum treatment on the uptake of other elements. Molybdenum is proved to be in an antagonist relationship with copper and sulphur, while molybdenum-phosphorus is a synergist interaction. However, in most of the plants we studied, increasing molybdenum-treatment enhanced cadmium uptake. We found the most significant cadmium accumulation in the case of pea, spinach and red beet.